2014
DOI: 10.5219/344
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of significant pigmets in green teas of different origin

Abstract: This work monitors flavonoid pigments (theaflavins and thearubigins), and chlorophyll in green teas from different growing regions (India, China, Russia, Vietnam). These pigments affect the quality of the finished tea infusion and their quantity is affected by the way of tea processing (fermentation). 15 samples of green loose teas were selected for the analysis. The content of these pigments was determined using UV-Vis spectrophotometry, the concentration of flavonoid pigments was measured at a wavelength of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
4
1
Order By: Relevance
“…The contents of β-carotene and lutein were 847.13±2.51 and 4.86±0.18 mg/kg in gardenia seed, 22,402.77±1,206.95 and 223.48±6.16 mg/kg in green tea, and 663.81 ±24.14 and 14.41±0.93 mg/kg in cactus pear, respectively. These values were higher than the previously reported values in gardenia seed (12.7 mg/kg; 14) and green tea (700 mg/kg; 15); such differences were thought to be due to different genotypes, cultivating conditions, and/or processing conditions (12,13).…”
Section: Resultscontrasting
confidence: 69%
See 1 more Smart Citation
“…The contents of β-carotene and lutein were 847.13±2.51 and 4.86±0.18 mg/kg in gardenia seed, 22,402.77±1,206.95 and 223.48±6.16 mg/kg in green tea, and 663.81 ±24.14 and 14.41±0.93 mg/kg in cactus pear, respectively. These values were higher than the previously reported values in gardenia seed (12.7 mg/kg; 14) and green tea (700 mg/kg; 15); such differences were thought to be due to different genotypes, cultivating conditions, and/or processing conditions (12,13).…”
Section: Resultscontrasting
confidence: 69%
“…Chlorophylls a and b were detected only in green tea powder at 59.46±0.77 and 151.91±7.26 mg/kg, respectively, which were lower than the reported values (11). A wide range of the chlorophyll contents in green tea depending on the cultivating area and processing method has been previously reported (12,13). Carotenoids detected in the food materials included β-carotene and lutein.…”
Section: Resultsmentioning
confidence: 59%
“…They found chlorophyll values averaging 1.4 mg per 1 g of dry substance. Ošťádalová et al (2014) reported the amount of chlorophyll in particular types of teas, coming from the same growing area, but from the 2013 harvest. They found chlorophyll values averaging 1.39 mg per 1 g of dry substance.…”
Section: Discussionmentioning
confidence: 99%
“…The samples prepared in this way were extracted for 15 minutes and then their absorbance was measured. In all cases, the measurement maximum absorption of the absorption spectrum was checked in a broader wavelength range (Ošťádalová et al 2014). …”
Section: Chlorophyll Determinationmentioning
confidence: 99%
“…The world's tea production exceeds 4 million tons per year and more than 2 billion people consume tea [ 1 ]. Tea, which contains high levels of antioxidants and can prevent many diseases including cardiovascular and cancer, has received more and more attention from people [ 2 ]. Photosynthesis is the determinant of productivity and the basis of plant growth and development, and an important source of carbon in plants.…”
Section: Introductionmentioning
confidence: 99%